Transferable antibiotic resistance elements in Haemophilus influenzae share a common evolutionary origin with a diverse family of syntenic genomic islands. - Mohd-Zain, Z; Turner, S; Cerdeño-Tárraga, A; Lilley, A; Inzana, T; Duncan, A; Harding, R; Hood, D; Peto, T; Crook, D (2004)
Transferable antibiotic resistance in Haemophilus influenzae was first detected in the early 1970s. After this, resistance spread rapidly worldwide and was shown to be transferred by a large 40- to 60-kb conjugative element. Bioinformatics analysis of the complete sequence of a typical H. influenzae conjugative resistance element, ICEHin1056, revealed the shared evolutionary origin of this element. ICEHin1056 has homology to 20 contiguous sequences in the National Center for Biotechnology Information database. Systematic comparison of these homologous sequences resulted in identification of a conserved syntenic genomic island consisting of up to 33 core genes in 16 beta- and gamma-Proteobacteria. These diverse genomic islands shared a common evolutionary origin, insert into tRNA genes, and have diverged widely, with G+C contents ranging from 40 to 70% and amino acid homologies as low as 20 to 25% for shared core genes. These core genes are likely to account for the conjugative transfer of the genomic islands and may even encode autonomous replication. Accessory gene clusters were nestled among the core genes and encode the following diverse major attributes: antibiotic, metal, and antiseptic resistance; degradation of chemicals; type IV secretion systems; two-component signaling systems; Vi antigen capsule synthesis; toxin production; and a wide range of metabolic functions. These related genomic islands include the following well-characterized structures: SPI-7, found in Salmonella enterica serovar Typhi; PAP1 or pKLC102, found in Pseudomonas aeruginosa; and the clc element, found in Pseudomonas sp. strain B13. This is the first report of a diverse family of related syntenic genomic islands with a deep evolutionary origin, and our findings challenge the view that genomic islands consist only of independently evolving modules.